Application of Ultrasonic Technology in Modifying Tapioca Starch for Improving the Quality of Gluten-Free Noodles - Clara Rosalinda; Oksilia Oksilia; Filli Pratama; Tri Wardani Widowati (Journal of Applied Agricultural Science and Technology, 2026)
Excessive gluten intake may provoke health problems in susceptible individuals, requiring gluten-free noodle substitutes. Tapioca possesses the potential to serve as an alternative to wheat flour; nevertheless, its inherent stickiness, propensity to soften, and limited elasticity require modification. This study utilized tapioca flour modified by ultrasound at two frequencies (20 kHz and 40 kHz) and three duration intervals (40, 45, and 50 minutes). The altered starch was subsequently employed to prepare noodles including a blend of rice flour, eggs, and salt. The measured metrics comprise texture, water absorption capacity, cooking loss, water solubility index (WSI), and swelling power. Data were examined utilizing ANOVA, followed by an LSD test at a 5% significance threshold. The findings indicated that both sonication frequency and duration significantly influenced all evaluated parameters. Raising the frequency to 40 kHz and extending the sonication duration to 50 minutes enhanced texture (121.50 gf), water absorption capacity (34.48%), water solubility index (WSI) (7.03%), and swelling power (4.05%), while concurrently increasing cooking loss to 58.47%. Ultrasonic modification has proven to be an eco-friendly technique for enhancing the functional attributes of tapioca, with prospective applications in the diversification of gluten-free noodle products.